Socialization on the Urgency of Establishing the Keujruen Blang Customary Institution Towards an Inclusive Farmer Community - Nellis Mardhiah; Nodi Marefanda; Alimas Jonsa; Fadli Afriandi (Universitas Lambung Mangkurat, 2024)
The people of Blang Geunang often face challenges in their profession as rice farmers. In Gampong Blang Geunang, the community experiences problems with crop failure caused by pests and diseases, limited knowledge, and conflicts with wildlife. Community service activities provide theoretical and practical knowledge to the people of Blang Geunang in the establishment of Keujruen Blang customary institutions. The method for implementing research-based community service activities is through a SMART approach that shows explicitly what will be achieved and how to achieve it. This activity is a Focus Group Discussion, which goes through the planning, implementation, and evaluation stages. This activity was held on October 4, 2023, in the Gampong Blang Geunang meeting hall. Participants who attended consisted of government elements (gampong, sub-district, and district), the Aceh Traditional Council, farmer groups, and the general public. This activity discovered that the Blang Geunang gampong does not yet have a Keujruen Blang traditional institution due to a lack of understanding of the laws and regulations and the Qanun as its derivative. This activity resulted in public awareness of the positive impact of the formation of traditional institutions on the profession of farming communities. The positive impacts obtained include clear regulations regarding rice field activities, the availability of solutions if conflicts occur, legal protection, and the management of rice fields based on local wisdom. Due to the magnitude of the impact felt, the community agreed to form the Keujruen Blang traditional institution. The presence of this traditional institution makes the community inclusive in the management of rice fields in Gampong Blang Geunang.